2014
DOI: 10.1155/2014/105120
|View full text |Cite
|
Sign up to set email alerts
|

Diethylcarbamazine Attenuates the Development of Carrageenan-Induced Lung Injury in Mice

Abstract: Diethylcarbamazine (DEC) is an antifilarial drug with potent anti-inflammatory properties as a result of its interference with the metabolism of arachidonic acid. The aim of the present study was to evaluate the anti-inflammatory activity of DEC in a mouse model of acute inflammation (carrageenan-induced pleurisy). The injection of carrageenan into the pleural cavity induced the accumulation of fluid containing a large number of polymorphonuclear cells (PMNs) as well as infiltration of PMNs in lung tissues and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…The effectiveness of DEC in the treatment of Tropical Pulmonary Eosinophilia (TPE) in clinical studies confirms this hypothesis and may be a potential indication for the use of this drug in other lung diseases such as COPD and ALI [3]. Recently, a number of studies have reported a marked anti-inflammatory property for DEC using asthma and acute lung injury models [4,5]. However, how DEC exerts this effect is still unknown, and no existing studies have investigated the effect of DEC in relation to key transcription factors that orchestrate the inflammatory response.…”
Section: Introductionmentioning
confidence: 69%
“…The effectiveness of DEC in the treatment of Tropical Pulmonary Eosinophilia (TPE) in clinical studies confirms this hypothesis and may be a potential indication for the use of this drug in other lung diseases such as COPD and ALI [3]. Recently, a number of studies have reported a marked anti-inflammatory property for DEC using asthma and acute lung injury models [4,5]. However, how DEC exerts this effect is still unknown, and no existing studies have investigated the effect of DEC in relation to key transcription factors that orchestrate the inflammatory response.…”
Section: Introductionmentioning
confidence: 69%
“…In the present study, diethylcarbamazine significantly reduced the AMI-induced COX-2 protein expression in rats. Ribeiro et al (31) demonstrated that diethylcarbamazine attenuates carrageenan-induced lung injury in rats via COX-2 and iNOS expression. .…”
Section: Discussionmentioning
confidence: 99%
“…Five sections (5 μ m in thickness) of each group were cut and adhered to slides treated with 3‐amino‐propyl‐trietoxi‐silane (Sigma). Then, the immunohistochemical assays were performed according to the methodology of Ribeiro et al . The antibodies used were anti‐IL‐1 β antibody (1 : 11 dilution; ab9722; Abcam, Cambridge, UK), anti‐IL‐17 (1 : 50 dilution; sc‐7927; SantaCruz Biotechnology, Santa Cruz, CA, USA), anti‐IL‐10 (1 : 50 dilution; ab33471; Abcam), anti‐iNOS (1 : 250 dilution; ab3523; Abcam), anti‐COX‐2 (1 : 400; ab15191; Abcam), and TGF‐ β (1 : 100 dilution; ab66043; Abcam).…”
Section: Methodsmentioning
confidence: 99%
“…Cyclooxygenases are enzymes involved in the conversion of arachidonic acid to prostaglandin H2, the precursor of various compounds that are important inflammatory mediators . Recent studies in our laboratory have exploited this anti‐inflammatory action of DEC …”
Section: Introductionmentioning
confidence: 99%